Emilia Pardo Bazan and Galician culture. «La muiñeira» edition - López Quintáns, Javier (Madrygal. Revista de Estudios Gallegos, 2014)
The article edites Pardo Bazán’s “La muiñera”. Galicia is introduced as a subject in her production. Finally, an annoted edition is proposed.
Keywords: edition; muiñeira; tradition; Galicia.